Mechanosensitive TREK-1 two-pore-domain potassium (K2P) channels in the cardiovascular system. (January 2021) - Wiedmann, Felix; Rinné, Susanne; Donner, Birgit; Decher, Niels; Katus, Hugo A.; Schmidt, Constanze
Abstract: TWIK-related K + channel (TREK-1) two-pore-domain potassium (K2P ) channels mediate background potassium currents and regulate cellular excitability in many different types of cells. Their functional activity is controlled by a broad variety of different physiological stimuli, such as temperature, extracellular or intracellular pH, lipids and mechanical stress. By linking cellular excitability to mechanical stress, TREK-1 currents might be important to mediate parts of the mechanoelectrical feedback described in the heart. Furthermore, TREK-1 currents might contribute to the dysregulation of excitability in the heart in pathophysiological situations, such as those caused by abnormal stretch or ischaemia-associated cell swelling, thereby contributing to arrhythmogenesis. In this review, we focus on the functional role of TREK-1 in the heart and its putative contribution to cardiac mechanoelectrical coupling. Its cardiac expression among different species is discussed, alongside with functional evidence for TREK-1 currents in cardiomyocytes. In addition, evidence for the involvement of TREK-1 currents in different cardiac arrhythmias, such as atrial fibrillation or ventricular tachycardia, is summarized. Furthermore, the role of TREK-1 and its interaction partners in the regulation of the cardiac heart rate is reviewed. Finally, we focus on the significance of TREK-1 in the development of cardiac hypertrophy, cardiac fibrosis and heart failure.